Comparative analysis of supercritical carbon dioxide and subcritical water extraction for Sabah Coffea canephore - Sarah Aisyah Khurun Hizar; Ceron Ezra Yangun; Noor Sabariah Mahat; Muhammad Abbas Ahmad Zaini; Jumardi Roslan; Rovina Kobun; Macdalyna Esther Ronie; Norazlina Mohammad Ridhwan; Nicky Rahmana Putra; Muhammad Syafiq Hazwan Ruslan; Amir Haziq Abdul Razak; Hasmadi Mamat; et al. (College of Engineering, Mustansyriah University, 2025)
This work provides a thorough comparative analysis of the green extraction process, viz. supercritical carbon dioxide and subcritical water extraction methods for Sabah Coffea canephore. Rigorous experiments were conducted using supercritical carbon dioxide (temperature ranging from 40 to 80 °C and pressure from 10 to 30 MPa) and subcritical water (temperature ranging from 120 to 180 °C with extraction times from 5 to 15 min). The optimum conditions for supercritical carbon dioxide extraction were obtained at 79 °C and 30 MPa at the maximum extract yield (8.549%), total phenolic content (4.563 mg/g gallic acid equivalent), total flavonoid content (0.763 mg/g quercetin equivalent) and antioxidant activity (63.34%). Meanwhile, subcritical water extraction is the best extraction method for Coffea canephore, which was obtained optimum conditions at 180 °C and 15 min of extraction time with a maximum extract yield of 44.477%, total phenolic content of 6.481 mg/g gallic acid equivalent, total flavonoid content of 13.816 mg/g quercetin equivalent and 77.586% of antioxidant activity. In conclusion, this understanding contributes to developing optimized conditions for green extraction methods, expanding the potential applications of Sabah Coffea canephore in industries, including pharmaceuticals and functional foods.